A statistical industrial approach for the synthesis conditions of zeolites using fly ash and kaolinite. Issue 1 (26th June 2017) - Ramírez‐Zamora, R.M.; Solís‐López, M.; Robles‐Gutierrez, I.; Reyes‐Vidal, Y.; Espejel‐Ayala, F.
Abstract : This work describes the statistical analysis carried out on studies of the synthesis of zeolites using fly ash (FA) and kaolinite and shows the main parameters in the hydrothermal synthesis of eight principal zeolites. The chosen zeolites were faujasite (zeolite X), zeolite A, zeolite P, hydroxysodalite, analcime, chabazite, hydroxycancrintie, and sodalite for FA and kaolinite. The statistical analysis consisted of analysis of variance (ANOVA) of the four principal parameters considered: temperature of synthesis, reaction time, Si/Al ratio of the FA and kaolinite and the solid/liquid ratio in the hydrothermal system. For the use of FA, zeolite P, zeolite X, and hydroxysodalite were the three principal synthesized zeolites in the majority of the studies while zeolite A, zeolite P, and sodalite where the three principal zeolites synthesized when kaolinite was used. In general terms, the use of FA required a low temperature and time of synthesis compared to the use of kaolinite. With regard to the Si/Al ratio, the values were similar in both cases, while the solid/liquid ratio for the use of FA was higher than that for kaolinite. Contrast analysis was carried out showing several differences in the synthesis of the eight types of analyzed zeolites. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 318–332, 2018